Emerging nanotechnologies in rechargeable energy storage systems - Rodriguez-Martinez, Lide M.; Omar, Noshin (Micro & nano technologies., 2017)
For those interested in materials and electrochemical cell development, this book provides focused coverage of the development, process, characterization techniques, modeling, safety and applications of nanomaterials for rechargeable energy storage systems --